Perlindungan Hukum bagi Pencipta dan Pemegang Hak Cipta Konten Kreator Instagram - Fetum Fetum (Postgraduate University of Merdeka Malang, 2021)
The goal to be achieved through this research is to identify, assess and analyze legal protection for creators and copyright holders of Instagram creator content, Copyright Holders and Instagram Content Creators get legal protection for creations and content created based on their original thoughts or ideas and creativity. into the Instagram platform in Indonesia. The type of research used to write this thesis uses normative legal research in the preparation of this scientific paper with a descriptive method, especially related to Law Number 28 of 2014 concerning Copyright and other supporting regulations. From the results of the research using the above method, the authors get answers to the existing problems that Copyright Holders and Instagram Content Creators get legal protection for creations and content created based on their original thoughts or ideas and creativity into the Instagram platform in Indonesia. In addition, the Copyright Law provides protection related to moral rights and economic rights, moral rights and economic rights are exclusive rights owned by creators or content creators that must be protected by the Copyright Law. Criminal sanctions for copyright infringement have provided legal protection for creators and copyright holders of Instagram creator content, this is regulated in the Copyright Law, which contains 8 (eight) provisions relating to criminal sanctions for copyright infringement, namely Article 112 to Article 119 of the Copyright Act. In this case, it is clear that there is a threat of criminal sanctions for people who deliberately steal other people's content, but the lack of legal information for Instagram content creators has made it impossible for people to be convicted under these provisions.DOI: https://doi.org/10.26905/mlj.v2i2.7163